Gambaran Respon Fisiologis Dan Psikologis Pada Pasien Yang Didiagnosa Infertil Di Klinik Sekar Rumah Sakit Umum Daerah Dr. Moewardi - Wardhani, Rosalina Kusuma; , Sulastri, S.Kp., M.Kes (2017)
Background: Infertile is the inability of married couples within a years. Infertile will be a very sensitive and difficult problem for married couples who have been married for a long time and have not had children. Infertility is a crisis in life that can affect various aspects. Based on the many couples experiencing fertility problems, would cause both physiological and psychological effects there are usually infertile couples tend to have feelings that can affect confidence and the image of him. Objective: This study aims to reveal the physiological and psychological responses in patients diagnosed infertile Clinic Hospital Dr. Sekar Moewardi. Methods: This study used a descriptive method with quantitative approach. The study was conducted during one month in Clinical Hospital Dr. Sekar Moewardi. The samples used by 74 respondents and taken by accidental sampling. Data collection techniques using questionnaires and data analysis using test descriptive Conclusion: Based on the results of research show that the description of the physiological response of patients diagnosed infertile Clinic Hospital Dr. Sekar Moewardi most are feeling a headache, cold hands and feet, frequent awakening during sleep and often feel tired and lethargic. While most of the psychological response is a feeling that children are a guarantee of security in the 2 future, their life feeling empty, feeling annoyed because no children, and envied by friends who are pregnant.